2010
DOI: 10.1097/bpo.0b013e3181e4f761
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Thoracolumbosacral Orthoses and SpineCor Treatment of Adolescent Idiopathic Scoliosis Patients Using the Scoliosis Research Society Standardized Criteria

Abstract: We were unable to identify any significant differences in brace treatment outcomes when comparing TLSO and SpineCor treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
0
36
0
2
Order By: Relevance
“…Today it is possible to find 5 studies respecting all these criteria [9,16-19]: looking at them as a whole, bracing seems to alter positively the natural history of AIS, and apparently best results can be achieved when the SOSORT criteria are satisfied [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Today it is possible to find 5 studies respecting all these criteria [9,16-19]: looking at them as a whole, bracing seems to alter positively the natural history of AIS, and apparently best results can be achieved when the SOSORT criteria are satisfied [2]. …”
Section: Introductionmentioning
confidence: 99%
“…With the variety of brace applications available today, there are different characteristics with varying outcomes. Independent studies have shown that soft braces have no advantage over rigid braces [5][6][7][8] . Rigid braces may be symmetric or asymmetric.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of Pilates, Araujo et al In studies that used some type of corrective brace for treatment of IS, 66.6% (two of three) reported improvement in progression of spine lateral inclination. Gammon et al (35) found a little increase in Cobb angle of 6.7° in patients with SpineCor brace and an increase of 4.8° in subjects with thoracolumbosacral orthoses. Negrini et al (37) found a statistically significant reduction (p < 0.05) of Cobb angle only in the groups wich associated the use of corrective braces (18,21 or 23 hours per day) to kinesiotherapy -except the group that used the Risser brace.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies with corrective brace, 66.7% showed or a reduction of the curve magnitude or a higher rate of subjects with improvement or stabilization of the curve; meanwhile only Gammon et et al (35) detected an increase in the Cobb angle after intervention. It is noteworthy that the study of Gammon et al (35) was the only one that did not use any kinesiotherapeutic technique in any of its treatment groups.…”
Section: Discussionmentioning
confidence: 99%